Assessment of Pavement Performance Using the Pavement Condition Index (PCI): A Case Study of the Bengrah II Project in Palembang, Indonesia - Armahedi, Aldi; Mulyati, Ely (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2025)
Road pavement condition is essential for ensuring the smooth mobilization of materials, heavy equipment, and personnel in large-scale construction projects. Excessive loading from project vehicles often accelerates pavement deterioration, as observed along Mayor Memet Sastra Wirya Street, the main access road for the multi-year Bengrah II Project in Palembang. This study evaluated pavement distress types types and severity levels using the Pavement Condition Index (PCI) method based on field observations, photographic documentation, and dimensional measurements of visible defects. The analysis produced PCI values ranging from 62 to 70, with an average PCI of 67, classifying the pavement as Good. The dominant types of distress were alligator cracking and surface deformation (bumps and sags), primarily caused by repetitive heavy vehicle loading and inadequate drainage conditions. Despite the overall good classification, localized structural deterioration indicates early functional decline of the pavement. These results highlight that continuous heavy traffic associated with construction activities significantly affects pavement performance. Therefore, preventive maintenance actions such as surface overlays, shallow patching, and stricter vehicle load control, are recommended to sustain road functionality and extend service life. The findings contribute to pavement management strategies and policy formulation for maintaining construction access roads under intensive loading conditions.